The power of phages: revolutionizing cancer treatment - Islam, Md. Sharifull; Fan, Jie; Pan, Fan (Frontiers in Oncology, 2023)
Cancer is a devastating disease with a high global mortality rate and is projected to increase further in the coming years. Current treatment options, such as chemotherapy and radiation therapy, have limitations including side effects, variable effectiveness, high costs, and limited availability. There is a growing need for alternative treatments that can target cancer cells specifically with fewer side effects. Phages, that infect bacteria but not eukaryotic cells, have emerged as promising cancer therapeutics due to their unique properties, including specificity and ease of genetic modification. Engineered phages can transform cancer treatment by targeting cancer cells while sparing healthy ones. Phages exhibit versatility as nanocarriers, capable of delivering therapeutic agents like gene therapy, immunotherapy, and vaccines. Phages are extensively used in vaccine development, with filamentous, tailed, and icosahedral phages explored for different antigen expression possibilities. Engineered filamentous phages bring benefits such as built in adjuvant properties, cost-effectiveness, versatility in multivalent formulations, feasibility of oral administration, and stability. Phage-based vaccines stimulate the innate immune system by engaging pattern recognition receptors on antigen-presenting cells, enhancing phage peptide antigen presentation to B-cells and T-cells. This review presents recent 2 phage therapy advances and challenges in cancer therapy, exploring its versatile tools and vaccine potential.